The utility of the best care always bundle for the prevention of ventilator associated pneumonia in patients with severe traumatic brain injury - Kruger, Andries (Division of General Surgery, 2026)
Introduction Severe traumatic brain injury (STBI) is a risk factor for ventilator-associated pneumonia (VAP). In STBI, VAP is associated with worse neurological outcomes. Aim Quantify the impact of the “Best Care Always Bundle” (BCAB) on VAP-rate in STBI patients. Methods Retrospective review of STBI patients 12-months before (cohort 1) and after (cohort 2) implementation of the VAP-BCAB. Primary outcome: VAP incidence after implementation of BCAB. Secondary outcomes: duration of mechanical ventilation (MV), Neurocritical care unit (NCCU) and hospital length of stay (LoS), mortality, tracheostomy rate, re-intubation rate, and antibiotic use. Adherence to VAP-BCAB and correlation with VAP-rate was also analysed. Results Incidence of VAP were 24,7% and 18,6% in cohort 1 and 2 respectively (p=0.163). Duration of MV 6,7 days (5,4-7,9) and 7,3 days (6,1-8,4) in cohort 1 and 2 respectively (p=0.520). NCCU LoS 10,7 days (8,9-12,4) and 10,4 days (8,9-11,8) in cohort 1 and 2 respectively (p=0.797). Hospital LoS 21,5 days (16,2-26,9) and 18,0 days (15,3-20,6) in cohort 1 and 2 respectively (p=0.246). Thirty tracheostomies (37,5%) were recorded in cohort 1, 33 (31,7%) in cohort 2 (p=0.219). Thirteen re-intubations (20%) were recorded in cohort 1, nine (10,2%) in cohort 2 (p=0.055). Patients with VAP were fewer (7%) in months with high adherence to the VAP-BCAB, compared to low adherence months (28%) (p=0.003). Conclusion The clinical utility of the VAP-BCAB for the prevention of VAPs in STBI patients was clear in this study but the significance could only be shown where adherence to the VAP-BCAB was high.